Pengembangan Ekonomi Lokal Melalui Sektor Pariwisata di Desa Serang, Kecamatan Karangreja, Kabupaten Purbalingga - Huda, Rojaul (Jurnal Aspirasi, 2020)
The poor population in Indonesia is still dominated by people living in rural areas reaching 15.15 million or 60.26% of the total national poor population in the first semester of 2019. One of the efforts made to reduce poverty in rural areas is local economic development (LED). Local economic development is a participatory process of the community, local government, and the private sector to increase local competitiveness through available resources with the aim of creating decent jobs and sustainable economic activities. Serang Village, Karangreja Subdistrict, Purbalingga Regency conducts the LED through the tourism sector. This research encourages describing the implementation of the LED through the Serang Village tourism sector. The research method used is descriptive qualitative. Based on this research, it is found that there are six aspects of local economic development in Serang Village through the tourism sector, namely the LED target group through the utilization of local resources, having accessibility and strategic locations, encouraging the development of innovation and collaboration with the community, there is a sustainable agenda in driving economic activity of the local community, village government provides development facilities and cooperation to the community and local businesses in the development of tourism in Serang Village, the last aspect is that tourism in the village of Serang is managed through clear rules and good management.AbstrakPenduduk miskin di Indonesia masih didominasi oleh penduduk yang tinggal di wilayah perdesaan mencapai  15,15 juta atau 60,26  persen dari total jumlah penduduk miskin nasional per semester I tahun 2019. Salah satu upaya yang dilakukan untuk menanggulangi kemiskinan di wilayah perdesaan adalah dengan pengembangan ekonomi lokal (PEL). Pengembangan ekonomi lokal merupakan proses dimana masyarakat, pemerintah lokal, dan pihak swasta bekerjasama menciptakan kondisi ekonomi yang lebih baik dan menciptakan lapangan kerja, dengan tujuan membangun kemampuan perekonomian di tingkat lokal yang berkelanjutan sebagai upaya meningkatkan taraf hidup masyarakat yang lebih baik. Desa Serang, Kecamatan Karangreja, Kabupaten Purbalingga melakukan pengembangan ekonomi lokal melalui sektor pariwisata. Penelitian ini bertujuan untuk mendiskripsikan bagaimana implementasi pengembangan ekonomi lokal melalui sektor parwisiata Desa Serang dilakukan. Artikel ini menggunakan metode penelitian kualitatif dengan jenis deskriptif. Berdasarkan penelitian ini diperoleh fakta bahwa pengembangan ekonomi lokal di Desa Serang melalui sektor pariwisata berjalan dengan baik serta memiliki peran pada peningkatan perekonomian masyarakat. Rekomendasi penelitian ini adalah meningkatkan kerjasama dengan pihak swasta atau investor dari luar desa.